KAUST-7-NH2 / PIM-1 mixed matrix membrane as well as preparation method and application thereof

By introducing amino groups into the mixed matrix membrane of KAUST-7 and PIM-1, the interface compatibility is enhanced, and the problem of poor compatibility between inorganic fillers and polymer matrix is ​​solved, and efficient gas separation performance, anti-aging and anti-aging are achieved. The improvement of plasticization performance has formed an excellent KAUST-7-NH2/PIM-1 hybrid matrix membrane.

CN119215703APending Publication Date: 2024-12-31JIANGSU UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411475928.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing mixed matrix membranes have poor compatibility between inorganic fillers and polymer matrix, resulting in insufficient anti-aging and plasticizing properties, which limits their application in the field of gas separation.

Method used

Enhance the interface compatibility between KAUST-7 and PIM-1 by introducing amino groups (KAUST-7-NH2), forming hydrogen bonds to improve the anti-aging and anti-plasticization properties of the film materials, and by preparing KAUST-7 -NH2/PIM-1 hybrid matrix membrane uses the interaction of the amino-functionalized KAUST-7 structure with PIM-1 to form a dense and defect-free membrane structure.

Benefits of technology

It significantly improves the selectivity of CO2/CH4, extends the service life of the film, reduces physical aging and plasticization, improves gas separation performance, and is simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215703A_ABST
    Figure CN119215703A_ABST
Patent Text Reader

Abstract

The invention discloses a KAUST-7-NH2 / PIM-1 mixed matrix membrane as well as a preparation method and application of the KAUST-7-NH2 / PIM-1 mixed matrix membrane. The mixed matrix membrane comprises a self-polymerized microporous polymer (PIM-1) and amino modified KAUST-7 (KAUST-7-NH2) filled in the matrix membrane. The KAUST-7-NH2 is filled into the PIM-1 solution to prepare a membrane casting solution, and the membrane casting solution is dried by a solution evaporation method to form the membrane. According to the present invention, the compatibility between KAUST-7-NH2 and PIM-1 is improved by introducing the amino group, the mechanical property of the membrane is significantly improved, the exposure of a large amount of CO2 adsorption active sites is promoted, the preferential adsorption of CO2 is enhanced, the CO2 permeability of the mixed matrix membrane is enhanced, and the CO2 / CH4 selectivity (PCO2 gt, 3219 Barrer, alphaCO2 / CH4 gt, 32.1) is improved; the preparation method provided by the invention is simple and easy to operate, and the prepared KAUST-7-NH2 / PIM-1 mixed matrix membrane has higher gas separation performance on the basis of excellent aging resistance and plasticizing resistance, and can be applied to efficient separation of CO2 / CH4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a KAUST-7-NH2 / PIM-1 mixed matrix membrane, a preparation method and application thereof. Background Art

[0002] Membrane separation has the advantages of being green, efficient, energy-saving, emission-reducing and simple to operate, and is increasingly widely used in the fields of energy, environmental protection, and chemical industry. It is difficult for traditional polymer membranes to simultaneously meet high gas permeability and separation selectivity, that is, it is difficult to break through the "upper bound" of polymer membranes. Although dense inorganic membranes can simultaneously obtain high permeation flux and high selectivity, inorganic materials are brittle, prone to defects, and expensive, which limits their wide industrial application. In order to overcome the limitations of the above membrane materials, mixed matrix membranes derived from adding nanoporous molecular sieves to polymers have attracted widespread attention. Such membranes have the advantages of high selectivity of nanoporous materials for molecular size and shape, as well as the processability and high mechanical strength of polymers. In addition, mixed matrix membranes also have the advantages of high thermal stability, plasticization resistance, and anti-aging. Therefore, mixed matrix membranes have become the focus of researchers.

[0003] Polymerized microporous polymer (PIM-1) is an emerging polymer material. Due to its unique microporous structure, it has a very high free volume fraction (FFV), high gas permeability and high selectivity, and is gradually considered to be one of the most competitive membrane materials. However, the separation performance of most PIM-1 membrane materials decreases with the increase of feed gas pressure (easy to plasticize), and the gas flux decreases with the extension of service time (easy to age), which limits the application of PIM-1 membrane materials.

[0004] KAUST-7 is a new type of porous material composed of ligands and metal ions. It has high adsorption selectivity for CO2, ultra-high specific surface area, high porosity, chemical stability and thermal stability, and has become a hot filler in mixed matrix membranes. However, these mixed matrix membranes generally have fatal defects. The poor interface compatibility between the two phases will produce non-selective pores, resulting in a significant decrease in gas selectivity.

[0005] In the present invention, an amino group (KAUST-7-NH2) is introduced, and the hydrogen of the amino group on the group forms a hydrogen bond with the nitrogen atom of the cyano group on PIM-1 and the oxygen atom on the chain segment, thereby enhancing compatibility, eliminating interface defects, improving CO2 / CH4 selectivity, and effectively improving the anti-aging and anti-plasticization properties of the membrane material. Thus, a KAUST-7-NH2 / PIM-1 mixed matrix membrane, a preparation method and an application thereof are proposed. Summary of the invention

[0006] The present invention provides a KAUST-7-NH2 / PIM-1 mixed matrix membrane, a preparation method and an application thereof, which overcome the defect in the prior art that the anti-aging and anti-plasticization properties of the membrane material cannot be effectively improved due to the poor compatibility between the inorganic filler and the polymer matrix.

[0007] The technical solutions adopted in the present invention are:

[0008] A method for preparing a KAUST-7-NH2 / PIM-1 mixed matrix membrane comprises the following steps:

[0009] 1) uniformly dispersing the required mass of KAUST-7-NH2 in a solvent by ultrasound to obtain a KAUST-7-NH2 suspension;

[0010] 2) dissolving the self-polymerized microporous polymer PIM-1 in a solvent and filtering to obtain a PIM-1 polymer solution;

[0011] 3) mixing the PIM-1 polymer solution and the KAUST-7-NH2 suspension evenly to obtain a casting solution;

[0012] 4) After the casting solution is degassed, it is poured into a mold to form a membrane, and then dried to remove the residual solvent, thereby finally obtaining a KAUST-7-NH2 / PIM-1 mixed matrix membrane.

[0013] Furthermore, the KAUST-7-NH2 has a two-dimensional flake morphology, and the mass fraction of the KAUST-7-NH2 suspension is 10 to 40 wt.%.

[0014] Furthermore, the preparation process of KAUST-7-NH2 is as follows:

[0015] a) firstly, pyrazine and 2-aminopyrazine ligand were added to 22 mL of ethanol / water (ethanol / water=6.3:1) mixed solution to prepare a precursor solution; then, 0.54 g of Ni(NO3)2·6H2O was added to the precursor solution, and the solution was ultrasonically treated for 20 min;

[0016] b) Dissolve 0.24 g of Nb2O5 in 2.5 mL of HF and heat in a water bath at 70°C for 4 h under stirring. When the reaction solution becomes clear, the inorganic fluorine-containing anion NbOF5 is obtained. 2- Solution (containing H2NbOF5);

[0017] c) mixing the two solutions of step a) and step b) together, and then vigorously stirring the mixed solution at room temperature for 2 hours;

[0018] d) The mixed solution obtained in step c) was added into a high temperature and high pressure resistant polytetrafluoroethylene liner (50 mL), and the polytetrafluoroethylene liner was placed into a high pressure reactor, and then placed in a 130°C oven (programmed temperature, 5°C min -1 ) react for 24 hours;

[0019] e) After the reaction is completed, the reaction is slowly cooled to room temperature, the solid product is collected by centrifugation, and washed with DI water and ethanol for 3 times;

[0020] f) drying the precipitated product obtained in step e) under vacuum at 150° C. for 24 h to obtain KAUST-7-NH 2 crystals.

[0021] Furthermore, the preparation process of the PIM-1 is as follows:

[0022] S1: Dissolve equimolar amounts of TTSBI (5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane) and TFTPN (tetrafluoroterephthalonitrile) in DMF (N,N-dimethylformamide), and stir the mixture for 30 min until it is completely dissolved;

[0023] S2: A certain amount of K2CO3 is quickly poured into the mixed solution of step S1), the mixed solution is placed in a vacuum device and evacuated, and nitrogen is introduced for protection, and the temperature is raised to 65°C under nitrogen atmosphere and stirred at a constant speed for continuous reaction for 72 hours.

[0024] S3: After the reaction is completed, the product is slowly cooled to room temperature, and a bright yellow precipitate is collected by suction filtration. Then, in order to remove the anhydrous potassium carbonate that has not participated in the reaction, the precipitate is washed with deionized water, and the precipitate is collected by suction filtration. The final product is placed in a vacuum drying oven for drying, and the above process is repeated multiple times;

[0025] S4: Purification by the "methanol recrystallization" method: the dried solid product is dissolved in chloroform, filtered naturally with filter paper, and the clarified solution is added dropwise into methanol with continuous stirring, and recrystallization occurs immediately; the precipitated bright yellow solid product is filtered with a funnel and dried, and the above operation is repeated several times. Finally, the obtained bright yellow precipitate is dried under vacuum at 100°C for 24 hours to finally obtain PIM-1.

[0026] Furthermore, the mass ratio of TFTPN, TTSBI, K2CO3 and DMF is 1:(1.5-2.0):(1.0-1.5):(30-35).

[0027] Furthermore, the solvent in step 1) or step 2) is selected from one of toluene, dichloromethane, chloroform, tetrahydrofuran, N,N-dimethylformamide or N-methylpyrrolidone, and the concentration of the PIM-1 polymer solution is 4-10wt.%.

[0028] Furthermore, in step 3), after the solutions are mixed evenly, the mixed solution is purged in a N2 atmosphere until all excess solvents are removed to obtain a casting solution.

[0029] Furthermore, in step 4), the degassing method adopts static, negative pressure or ultrasonic degassing; the drying adopts vacuum drying, first vacuum drying at 40-70°C for 12-48h, and then the temperature is raised to 100-150°C and vacuum drying for 12-48h.

[0030] The invention also discloses a KAUST-7-NH2 / PIM-1 mixed matrix membrane, which is prepared by adopting the above method.

[0031] Furthermore, the thickness of the mixed matrix membrane is 40-100 μm.

[0032] The invention also discloses an application of KAUST-7-NH2 / PIM-1 mixed matrix membrane in the field of CO2 gas separation.

[0033] The present invention has the following beneficial effects:

[0034] 1) The present invention introduces amino groups into the KAUST-7 skeleton by means of mixed ligands to synthesize a novel amino-functionalized KAUST-7 structural material (KAUST-7-NH2). The morphology of the crystal is adjusted to a two-dimensional sheet by adjusting the amount of the ligand 2-aminopyrazine, and the crystal is introduced into the PIM-1 matrix to prepare a mixed matrix membrane. The interfacial compatibility of the two is enhanced by intermolecular interactions such as charge transfer and hydrogen bonding to form a dense and defect-free mixed matrix membrane, thereby achieving improved separation performance and effectively improving the anti-aging and anti-plasticization properties of the membrane material. Specifically, PIM-1 molecular chains are interspersed in the KAUST-7-NH2 crystal network structure, forming narrow sub-nanoscale micropores inside the KAUST-7-NH2 channels, thereby improving the gas molecule sieving performance of the mixed matrix membrane; the hydrogen of the amino group on this group forms hydrogen bonds with the nitrogen atom of the cyano group on PIM-1 and the oxygen atom on the chain segment, thereby enhancing the interaction between PIM-1 and KAUST-7-NH2 fillers in the membrane material, limiting the movement of the PIM-1 molecular chain, increasing the difficulty of the rotation of the PIM-1 molecular chain, and hindering the migration between polymer chains, thereby reducing the physical aging rate and CO2-induced plasticization of the KAUST-7-NH2 / PIM-1 mixed matrix membrane.

[0035] 2 The preparation method provided by the present invention is simple and easy to operate. The prepared KAUST-7-NH2 / PIM-1 mixed matrix membrane has high gas separation performance on the basis of excellent anti-aging and anti-plasticization properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a comparison diagram of the mixed matrix membranes and the Robeson upper limit in Examples 1-2 and Comparative Example 1;

[0037] Figure 2 are SEM cross-sectional images of PIM-1 mixed matrix membranes with different KAUST-7-NH2 loading amounts in Examples 1-2 and Comparative Example 1;

[0038] Figure 3 is a graph showing the relationship between the gas permeability coefficient and pressure of the mixed matrix membranes prepared in Example 1 and Comparative Example 1;

[0039] Figure 4 Graph showing the change in gas permeability coefficient of the mixed matrix membrane in Experimental Example 1 and Comparative Example 1 over time. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with the accompanying drawings.

[0041] In order to further improve the selective separation performance, anti-plasticization and anti-aging performance of MOF-based mixed matrix membranes, the present invention introduces amino groups into the KAUST-7 skeleton by means of mixed ligands, synthesizes a new KAUST-7 structural material (KAUST-7-NH2) with amino functionalization, adjusts the amount of the added ligand 2-aminopyrazine to adjust the morphology of the crystal, and introduces it into the PIM-1 matrix to prepare a mixed matrix membrane.

[0042] The amino groups on KAUST-7 can react reversibly with CO2, thereby selectively promoting the transfer of CO2 within the membrane and improving the compatibility between KAUST-7-NH2 and the PIM-1 matrix.

[0043] The present invention is based on the rational design and construction of efficient hybrid matrix metal-organic framework membranes based on three interlocking criteria:

[0044] (i) The amino-functionalized fluorinated metal organic framework KAUST-7-NH2 acts as a molecular sieve adsorbent to selectively enhance CO2 diffusion while rejecting methane;

[0045] (ii) adjusting the crystal morphology to nanosheets with the most exposed (001) crystal planes;

[0046] (iii) The (001) nanosheets are aligned in-plane in the polymer matrix.

[0047] The membrane showed a very high separation rate of CO2 from CO2 / CH4 mixed gas under actual working conditions. In addition, KAUST-7-NH2 provided rigid support for the PIM-1 matrix, preventing the migration of molecular chains and reducing the physical aging rate of the KAUST-7-NH2 / PIM-1 mixed matrix membrane and the plasticization induced by CO2.

[0048] Therefore, amino groups were introduced into the KAUST-7 skeleton by means of mixed ligands, and an amino transfer pathway was constructed in the membrane, which resulted in higher CO2 separation performance on the basis of excellent anti-aging and anti-plasticization properties.

[0049] The permeability coefficient and selectivity test process of the following examples and comparative examples are as follows: Under the operating conditions of 35°C and 0.2MPa, the KAUST-7-NH2 / PIM-1 mixed matrix membrane was tested for permeability performance, and the mixed gas composition was CO2 / CH4: 50 / 50 volume percent. Its permeability performance was obtained by constant pressure-variable volume method.

[0050] For the mixed gas test, the upstream mixed gas enters the top of the permeation cell through a pressure reducing valve, a filter and a rotary valve, and the pressure is adjusted by a back pressure controller. The gas permeates through the mixed matrix membrane in the permeation cell to the bottom, and helium is used as a purge gas to blow the permeate gas into the gas chromatograph to detect the concentration of each component, and the gas flux is measured by a soap bubble flowmeter. In all tests, the "stage-cut" (i.e., the ratio of permeate flow to feed flow) is maintained at less than 1% to avoid concentration polarization. Before testing, all other gases in the pipeline and membrane are evacuated with a vacuum pump.

[0051] Calculation of gas permeability coefficient and selectivity in mixed matrix membranes:

[0052]

[0053] Where A and B represent different gases. i is the permeability coefficient of gas i in the membrane, the unit is Barrer (1Barrer = 1×10 -10 cm 3 (STP)cm / (cm 2 sec cmHg)); L is the thickness of the film, cm; N i is the gas permeation flux, cm 3 / sec; A is the effective membrane area, cm 2 ;Δp i is the pressure difference across the membrane, cmHg; x i ,y i represent the molar concentrations of permeate gas and feed gas respectively.

[0054] Example 1

[0055] a) Accurately weigh 0.1285 g of dry KAUST-7-NH2 filler and add it to 4 mL of chloroform solution, disperse it by ultrasonication for 20 min, and then stir it for 4 h to make the KAUST-7-NH2 filler evenly dispersed in the chloroform solution to form a uniform KAUST-7-NH2 chloroform solution;

[0056] b) Accurately weigh 0.3 g of dry PIM-1 powder, take 0.03 g of the weighed PIM-1 and add it to the KAUST-7-NH2 chloroform solution in step a), stir for 2 h until completely dissolved, then add the remaining PIM-1 powder to the solvent, stir for 12 h until completely dissolved, to obtain a uniformly dissolved casting solution, and then perform ultrasonic degassing;

[0057] c) Pour the degassed casting solution into a polytetrafluoroethylene culture dish with a diameter of 6 cm, place it horizontally, and place a glass funnel on the polytetrafluoroethylene culture dish. Wait for the solvent to evaporate to form a film under room conditions. Then put the formed film together with the membrane mold into a 70°C vacuum drying oven and dry it for 24 hours. Then increase the temperature to 150°C and dry it for 48 hours to obtain a mixed matrix membrane with a KAUST-7-NH2 content of 10 wt.% and a thickness of 40 to 100 μm.

[0058] Comparative Example 1

[0059] a) Accurately weigh 0.3 g of dry PIM-1 powder and add it to a clean brown reagent bottle, then use a pipette to accurately measure 4 mL of chloroform solution into the brown reagent bottle, stir magnetically for 12 h until PIM-1 is completely dissolved to form a uniform transparent solution, and then degas by ultrasonication;

[0060] b) Pour the solution after ultrasonic degassing into a polytetrafluoroethylene culture dish with a diameter of 6 cm, place it horizontally, and place a glass funnel on the polytetrafluoroethylene culture dish. Wait for the solvent to evaporate to form a film at room temperature. Then put the formed film together with the membrane mold into a 70°C vacuum drying oven and dry it for 24 hours. Then increase the temperature to 150°C and dry it for 48 hours to obtain a pure PIM-1 film with a thickness of 40 to 100 μm.

[0061] At 35°C and 0.2 MPa, the mixed matrix membrane prepared in Example 1 was tested for gas separation performance, and the permeability coefficients of CO2 and CH4 were 3219.0 Barrer and 100.3 Barrer, respectively. The selectivity of CO2 to CH4 is: CO2 / CH4=32.1. Similarly, at 35°C and 0.2MPa, the pure PIM-1 membrane prepared in Comparative Example 1 was tested for gas separation performance, and the permeability coefficients of CO2 and CH4 were 3945.0 Barrer and 315.6 Barrer, respectively. The selectivity of CO2 to CH4 is: CO2 / CH4 = 12.5. By comparing the gas separation performance of the membranes prepared in Example 1 and Comparative Example 1, it can be found that after adding KAUST-7-NH2 to the PIM-1 membrane, CO2 and CH4 can be effectively separated and purified.

[0062] Example 2

[0063] a) Accurately weigh 0.033 g, 0.075 g, and 0.2143 g of dry KAUST-7-NH2 filler, and add them to three dry and clean brown reagent bottles, respectively. Then use a pipette to accurately transfer 4 mL of chloroform solution to the three reagent bottles, ultrasonically disperse for 15 min, and then magnetically stir for 4 h until the KAUST-7-NH2 filler is uniformly dispersed in the chloroform solution to form a uniform KAUST-7-NH2 solution;

[0064] b) accurately weigh 3 portions of 0.3 g dried PIM-1 powder, take one tenth of each portion and add it to the KAUST-7-NH2 solution in step a), stir until completely dissolved, then add the remaining PIM-1 powder to their respective corresponding reagent bottles, stir for 12 hours until completely dissolved, and finally obtain casting solutions with KAUST-7-NH2 contents of 20 wt.%, 30 wt.%, and 40 wt.%;

[0065] c) Pour the degassed casting solution into a polytetrafluoroethylene culture dish with a diameter of 6 cm, place it horizontally, and place a glass funnel on top of the polytetrafluoroethylene culture dish. Wait for the solvent to evaporate to form a film under room conditions. Then put the formed film together with the membrane mold into a 70°C vacuum drying oven and dry it for 24 hours. Then increase the temperature to 150°C and dry it for 48 hours to obtain three mixed matrix membranes with a thickness of 40 to 100 μm.

[0066] The mixed matrix membrane prepared in Example 2 was tested for gas separation performance at 35° C. and 0.2 MPa. The test results are shown in Table 1.

[0067] Table 1 Mixed gas permeability of CO2 / CH4 system

[0068]

[0069] It can be seen from Table 1 that the CO2 and CH4 permeation fluxes of KAUST-7-NH2 / PIM-1 mixed matrix membranes continuously decrease with the increase of KAUST-7-NH2.

[0070] The decrease in permeation flux can be attributed to two main reasons: on the one hand, the tight binding between KAUST-7-NH2 and PIM-1 leads to a decrease in the mobility of the polymer segments; on the other hand, the rigid KAUST-7-NH2 occupies the effective channels available for gas transmission, increasing the curvature of the gas diffusion path. The selectivity of CO2 / CH4 increases first and then decreases. When the KAUST-7 loading is increased to 30wt.%, the permeability of CO2 decreases slightly, while the permeability of CH4 decreases significantly, which significantly improves the selectivity of CO2 / CH4.

[0071] The above results show that due to the limited Langmuir adsorption sites and exclusion effect, CO2 preferentially adsorbs and penetrates the membrane, significantly hindering the transmission of CH4. The CO2 permeation flux of the 30wt.% KAUST-7-NH2 / PIM-1 mixed matrix membrane is 3219 Barrer, and the CO2 / CH4 selectivity is 32.1, which are 0.8 and 2.6 times that of the original membrane, respectively. In addition, the improvement in selectivity also proves that the KAUST-7-NH2-based mixed matrix membrane is defect-free.

[0072] However, when the loading of KAUST-7-NH2 increases to 40wt.%, the CO2 / CH4 selectivity drops to about 23.5, while the permeation fluxes of CO2 and CH4 still decrease. This is mainly attributed to the serious aggregation of excessive fillers, which leads to non-selective interface defects that allow gas molecules to bypass. Its performance has exceeded the Robeson upper limit (such as Figure 1 ), indicating that the mixed matrix membrane has very ideal permeation separation performance when separating the above gas systems. The "Robeson upper bound" here is a graph formed by American scholar Robeson (Robeson LM, The upper bound revisited, Journal of Membrane Science, 2008, 320, 390-400) based on a large number of reported polymer membrane permeability data for specific gas molecules, with the permeability coefficient of CO2 as the horizontal axis and the selectivity of CO2 / CH4 as the vertical axis after data processing.

[0073] The scanning electron microscopy images of the mixed matrix membranes prepared in Examples 1 to 2 and Comparative Example 1 are shown in Figure 2 The anti-plasticization properties of the mixed matrix films prepared in Example 1 and Comparative Example 1 are shown in Figure 3 The (related) permeability coefficients of the mixed matrix membranes prepared in Example 1 and Comparative Example 1 for CO2 and CH4 gases and the (related) permeability selectivity for mixed gases after 150 days of aging are shown in the figure. Figure 4 (a~c).

[0074] like Figure 1 As shown in (a, a1), the PIM-1 membrane presents a uniform network structure without any visible defects, which is consistent with the typical appearance of glassy polymer membranes. For the KAUST-7-NH2 / PIM-1 mixed matrix membrane, when the loading amount of KAUST-7 is 10-40wt.%, all KAUST-7-NH2 fillers maintain their structural integrity and are evenly distributed in the PIM-1 matrix. Even at high loading, the KAUST-7-NH2 fillers are still tightly surrounded by the PIM-1 matrix, and no obvious interfacial defects (such as "sieves in cages") are found, which means that there is good interfacial adhesion between PIM-1 and KAUST-7-NH2. The above results are attributed to the strong intermolecular interactions (such as charge transfer, π-π stacking and hydrogen bonding) between the KAUST-7-NH2 fillers and the PIM-1 chains. In addition, the presence of polymer veins also proves the strong interfacial interaction between the KAUST-7-NH2 fillers and the PIM-1 matrix.

[0075] like Figure 3 As shown, with the increase of feed pressure, the CO2 permeance and CO2 / CH4 selectivity of PIM-1 membrane decreased by 37.0% and 32.0%, respectively, while the CO2 permeance and CO2 / CH4 selectivity of KAUST-7-NH2 / PIM-1 (30wt.%) membrane decreased by 8.6% and 8.7%, respectively. In addition, for these two feed gases, the permeation flux of KAUST-7-NH2 / PIM-1 (30wt.%) mixed matrix membrane decreased much slower than that of PIM-1 membrane. The enhanced anti-plasticization performance of 30wt.% KAUST-7-NH2 / PIM-1 mixed matrix membrane may be due to the rigid support of KAUST-7-NH2 on the polymer chains, thereby reducing their fluidity.

[0076] like Figure 4 As shown in (ab), after 150 days, the CO2 permeance and CH4 permeation flux of the PIM-1 membrane decreased by 66% and 67.7%, respectively. This may be due to the fact that during the separation process, the smaller free volume pores remain unchanged, while the larger free volume pores continue to collapse with physical aging. This causes the permeation flux of the larger diameter gas (CH4) to drop sharply over time, while the smaller diameter gas (CO2) drops more slowly.

[0077] like Figure 4As shown in (c), due to the improvement of the molecular sieving ability of the PIM-1 matrix, the gas selectivity slowly increases with the extension of aging time. In contrast, since the KAUST-7-NH2 filler provides rigid support for the PIM-1 matrix, it effectively prevents the collapse of the molecular chain, thereby improving the overall rigidity of the PIM-1 matrix. This makes the KAUST-7-NH2 / PIM-1 membrane exhibit stable gas permeability during the separation process, and the permeability coefficient and selectivity do not change significantly. The CO2 permeation flux and CH4 permeability of the 30wt.% KAUST-7-NH2 / PIM-1 mixed matrix membrane decreased by 7.7% and 25.2% respectively within 150 days. In summary, the KAUST-7-NH2 / PIM-1 membrane has excellent anti-plasticization and anti-aging properties.

[0078] Example 3

[0079] Based on Examples 1 and 2, the preparation process of KAUST-7-NH2 is:

[0080] a) firstly, pyrazine and 2-aminopyrazine ligand were added to 22 mL of ethanol / water (ethanol / water=6.3:1) mixed solution to prepare a precursor solution; then, 0.54 g of Ni(NO3)2·6H2O was added to the precursor solution, and the solution was ultrasonically treated for 20 min;

[0081] b) Dissolve 0.24 g of Nb2O5 in 2.5 mL of HF and heat in a water bath at 70°C for 4 h under stirring. When the reaction solution becomes clear, the inorganic fluorine-containing anion NbOF5 is obtained. 2- Solution (containing H2NbOF5);

[0082] c) mixing the two solutions of step a) and step b) together, and then vigorously stirring the mixed solution at room temperature for 2 hours;

[0083] d) The mixed solution obtained in step c) was added into a high temperature and high pressure resistant polytetrafluoroethylene liner (50 mL), and the polytetrafluoroethylene liner was placed into a high pressure reactor, and then placed in a 130°C oven (programmed temperature, 5°C min -1 ) react for 24 hours;

[0084] e) After the reaction is completed, the reaction is slowly cooled to room temperature, the solid product is collected by centrifugation, and washed with DI water and ethanol for 3 times;

[0085] f) drying the precipitated product obtained in step e) under vacuum at 150° C. for 24 h to obtain KAUST-7-NH 2 crystals.

[0086] The preparation process of PIM-1 is as follows:

[0087] S1: Dissolve equimolar amounts of TTSBI (5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane) and TFTPN (tetrafluoroterephthalonitrile) in DMF (N,N-dimethylformamide), and stir the mixture for 30 min until it is completely dissolved;

[0088] S2: A certain amount of K2CO3 is quickly poured into the mixed solution of step S1), the mixed solution is placed in a vacuum device and evacuated, and then nitrogen is introduced for protection, the temperature is raised to 65°C under a nitrogen atmosphere, and the reaction is continued for 72 hours with constant stirring; the mass ratio of TFTPN, TTSBI, K2CO3, and DMF is 1:(1.5-2.0):(1.0-1.5):(30-35).

[0089] S3: After the reaction is completed, the product is slowly cooled to room temperature, and a bright yellow precipitate is collected by suction filtration. Then, in order to remove the anhydrous potassium carbonate that has not participated in the reaction, the precipitate is washed with deionized water, and the precipitate is collected by suction filtration. The final product is placed in a vacuum drying oven for drying, and the above process is repeated multiple times;

[0090] S4: Purification by the "methanol recrystallization" method: the dried solid product is dissolved in chloroform, filtered naturally with filter paper, and the clarified solution is added dropwise into methanol with continuous stirring, and recrystallization occurs immediately; the precipitated bright yellow solid product is filtered with a funnel and dried, and the above operation is repeated several times. Finally, the obtained bright yellow precipitate is dried under vacuum at 100°C for 24 hours to finally obtain PIM-1.

[0091] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a KAUST-7-NH2 / PIM-1 mixed matrix membrane, characterized in that: The following steps are involved: 1) uniformly dispersing the required mass of KAUST-7-NH2 in a solvent by ultrasound to obtain a KAUST-7-NH2 suspension; 2) dissolving the self-polymerized microporous polymer PIM-1 in a solvent and filtering to obtain a PIM-1 polymer solution; 3) mixing the PIM-1 polymer solution and the KAUST-7-NH2 suspension evenly to obtain a casting solution; 4) After the casting solution is degassed, it is poured into a mold to form a membrane, and then dried to remove the residual solvent, thereby finally obtaining a KAUST-7-NH2 / PIM-1 mixed matrix membrane.

2. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 1, characterized in that: The KAUST-7-NH2 has a two-dimensional flake morphology, and the mass fraction of the KAUST-7-NH2 suspension is 10-40 wt.%.

3. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 1, characterized in that: The preparation process of KAUST-7-NH2 is as follows: a) firstly adding pyrazine and 2-aminopyrazine ligand into an ethanol / water mixed solution to prepare a precursor solution, then adding Ni(NO3)2·6H2O into the precursor solution, and ultrasonically treating the solution; b) Dissolve Nb2O5 in HF and heat in a water bath under stirring. After the reaction solution becomes clear, the inorganic fluorine-containing anion NbOF5 is obtained. 2- Solution; c) mixing the two solutions of step a) and step b) together, and then vigorously stirring the mixed solution at room temperature; d) adding the mixed solution finally obtained in step c) into a polytetrafluoroethylene liner, placing the polytetrafluoroethylene liner into a high-pressure reactor, and then placing it in an oven for reaction; e) After the reaction is completed, the reaction is slowly cooled to room temperature, the solid product is collected by centrifugation, and washed with DI water and ethanol several times; f) vacuum drying the precipitated product obtained in step e) to obtain KAUST-7-NH2 crystals.

4. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 1, characterized in that: The preparation process of PIM-1 is as follows: S1: Dissolve equimolar amounts of TTSBI and TFTPN in DMF and stir the mixture until completely dissolved; S2: Pour K2CO3 into the mixed solution of step S1), place the mixed solution in a vacuum device, evacuate it, introduce nitrogen protection, heat it and stir it under nitrogen atmosphere for continuous reaction; S3: After the reaction is completed, the product is cooled to room temperature, filtered to obtain a precipitate, then washed with deionized water, filtered to obtain the precipitate, and the final product is dried in a vacuum drying oven, and the above process is repeated multiple times; S4: Dissolve the dried solid product in chloroform, filter and add the clarified solution dropwise into methanol with constant stirring, and recrystallization will occur immediately; filter the precipitated solid product with a funnel and dry it, repeat the above operation several times, and finally dry the obtained bright yellow precipitate in a vacuum environment.

5. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 4, characterized in that: The mass ratio of TFTPN, TTSBI, K2CO3 and DMF is 1:(1.5-2.0):(1.0-1.5):(30-35).

6. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 1, characterized in that: The solvent in step 1) or step 2) is selected from one of toluene, dichloromethane, chloroform, tetrahydrofuran, N,N-dimethylformamide or N-methylpyrrolidone, and the concentration of the PIM-1 polymer solution is 4-10wt.%.

7. The method for preparing the KAUST-7-NH2 / PIM-1 mixed matrix membrane according to claim 1, characterized in that: In step 3), after the solutions are mixed evenly, the mixed solution is purged in a N2 atmosphere until all excess solvents are removed to obtain a casting solution.

8. A KAUST-7-NH2 / PIM-1 mixed matrix membrane prepared according to any one of claims 1 to 7.

9. The mixed matrix membrane of claim 8, wherein: The thickness of the mixed matrix membrane is 40-100 μm.

10. Use of the KAUST-7-NH2 / PIM-1 mixed matrix membrane as claimed in claim 8 in the field of CO2 gas separation.

Citation Information

Cited By

  • Mixed matrix membrane containing cyano modified KAUST-7 as well as preparation method and application of mixed matrix membrane

    CN120532314A